Spectral Assignment of Lysozyme Collective Vibrations - Deng, Y. T.; McKinney, J.; Romo, T.; Grossfield, A.; Markelz, A. (Biophysical Journal, 2019)
Global structural vibrations at terahertz (THz) frequencies have been associated with protein function and allosteric control. A chief obstacle to utilizing this control mechanism has been measurement of specific motions. Recently it was shown that while the vibrational density of states, and isotropic absorption spectra are broad and featureless, collective vibrations can be isolated based on their directionality using aligned samples (realized with protein crystals) and anisotropic THz microscopy [1]. However the assignment of resonant bands to specific structural motions was complicated by the high symmetry of the tetragonal crystals used, and the slow experimental method. To structurally map the vibrations of the chicken egg white lysozyme (CEWL) we measure anisotropic absorption of triclinic crystals using our new technique: ideal polarization varying anisotropic THz microscopy (IPV-ATM). The low symmetry triclinic crystals provide absolute protein orientation, and the near field IPV-ATM rapidly measures broadband terahertz linear dichroism of the microcrystals. All measurements were performed at room temperature under 100% humidity conditions. The unit cell parameters of triclinic lysozyme nitrate crystals, α = 28.5A°, b = 32.7A°, c = 35.1A°, α = 88.2°, β = 108.9°, γ = 111.9°, belonging to the P1 space group, were determined by X-ray diffraction before and after THz measurements. The intramolecular vibrational absorbance of the triclinic crystals has a more complex polarization dependence than the higher symmetry tetragonal crystals, as expected. While the tetragonal crystals have two strong bands at 45cm−1 and 55cm−1, the triclinic crystals have a series of narrow bands between 40 and 60cm−1 and a prominent band at 30cm−1. We compare the measured spectra to normal mode ensemble averaged calculations to assign the observed resonances, and isolating which collective motions impact the catalytic site.
Keywords: Biophysics